THE USE OF CLOZAPINE IN PAKISTAN: A STUDY BASED ON CLOZARIL PATIENTS MONITORING SYSTEM (CPMS): USE OF CLOZAPINE IN PAKISTAN: A STUDY BASED ON CLOZAPINE PATIENT MONITORING SYSTEM (CPMS) - Rehman, Raza Ur; Farooq , Saeed (Journal of Pakistan Psychiatric Society, 2025)
Treatment options for treatment-resistant schizophrenia include clozapine, a medication often reserved for refractory cases due to its unique efficacy and potential side effects. In developing countries no systematic data is available on Clozapine and its monitoring. OBJECTIVE: The current study aimed to provide data on Clozapine monitoring. METHOD The database of Clozapine Monitoring System of Novartis Pakistan was approached, and recorded medical history was analysed. Generic Clozaril was excluded from the study due to non-availability of monitoring data. RESULTS The study investigated 1256 patients from across Pakistan. Majority of the participants were male (70%). 230 mg was the average dosage of the drug during maintenance. Around 25% of the psychiatrists were prescribing the drug. CONCLUSION Clozaril is underprescribed in Pakistan, and possible reasons for this underutilisation of the medicine may include a lack of monitoring system that comes on top of a scarcity of psychiatric services and myths about the drug and its monitoring.